The Role Of The Tni Is To Achieve The Election Of The Regional Head Of The Governor Of Central Java, General, Free, Secret, Honest And Fair - Rifai Siregar, Ahmad (CV. Inara, 2022)
The TNI is required to be able to carry out its duties and functions in accordance with applicable laws. In this case, the TNI must be able to carry out its role in guarding the Indonesian nation's democratic party so that it can run smoothly and safely. It is undeniable that there are still unscrupulous members of the TNI who commit violations in the Pilkada, resulting in public statements related to the existence of government institutions that are not neutral, thus forming public opinion on the performance of the TNI. The formulation of the problem in the research is (1)What is the role of the TNI in realizing the Election of the Regional Head of the Governor of Central Java which is direct, general, free, confidential, honest and fair? (2) Why does the TNI need to maintain and realize a direct, general, free, secret, honest and fair election for the Regional Head of the Governor of Central Java? (3) What is the ideal concept expected for the TNI to realize the Election of the Regional Head of the Governor of Central Java which is direct, general, free, confidential, honest and fair? The approach used is sociological juridical, which means that this research is studied with laws and regulations and legal norms in accordance with the problems that exist in the field. Based on the results of the study, data were obtained that (1) The role of the TNI in the Regional Head Elections in Indonesia in the field of security was in principle an assistance to the Police. (2) The TNI needs to carry out its role in the Pilkada to protect against threats and disturbances that may arise in the holding of the Pilkada together with the National Police based on the law to carry out the duties of Kamtibmas. (3) The TNI must be able to put forward its professionalism as a TNI soldier in accordance with its identity, based on state politics and not taking sides with any group. Therefore, it is necessary to create ideal conditions so that they can be used to increase public trust and increase soldiers' understanding of the neutrality of the TNI.